2021
DOI: 10.1021/acssuschemeng.1c06685
|View full text |Cite
|
Sign up to set email alerts
|

SERS Enhancement of Porphyrin-Type Molecules on Metal-Free Cellulose-Based Substrates

Abstract: The detection of analytes using spectroscopy methods, such as surface-enhanced Raman spectroscopy (SERS), is crucial in the fields of medical diagnostics, forensics, security, and environmental monitoring. In recent years, a lot of focus has been directed toward organic polymer material-based SERS platforms due to their lower cost, controllable synthesis and fabrication, structural versatility, as well as biocompatibility and biodegradability. Here, we report that cellulose nanofiber-based substrates can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Although individual studies on the use of cellulose-based templates for fluorescence signal enhancement of specific molecules have been done, no approach showing that a wide variety of probe molecules can be enhanced using a metal-free biomaterial has been demonstrated. Additionally, we have previously shown that metal-free cellulose nanofibers can be used as substrates for the detection of porphyrin-type molecules via SERS, making cellulose-based platforms promising candidates for fluorescence enhancement . In this study, we show that the fluorescence signal from an extensive range of molecules including important biomolecules can be enhanced.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although individual studies on the use of cellulose-based templates for fluorescence signal enhancement of specific molecules have been done, no approach showing that a wide variety of probe molecules can be enhanced using a metal-free biomaterial has been demonstrated. Additionally, we have previously shown that metal-free cellulose nanofibers can be used as substrates for the detection of porphyrin-type molecules via SERS, making cellulose-based platforms promising candidates for fluorescence enhancement . In this study, we show that the fluorescence signal from an extensive range of molecules including important biomolecules can be enhanced.…”
Section: Introductionmentioning
confidence: 54%
“…Additionally, we have previously shown that metal-free cellulose nanofibers can be used as substrates for the detection of porphyrin-type molecules via SERS, making cellulose-based platforms promising candidates for fluorescence enhancement. 33 In this study, we show that the fluorescence signal from an extensive range of molecules including important biomolecules can be enhanced. The enhancement factors of molecules deposited on pristine CNF can reach values up to 120 and are comparable to those usually reported for noble metals (1−2 orders of magnitude for silver) 34,35 and can be further boosted by the application of UV light irradiation.…”
Section: ■ Introductionmentioning
confidence: 66%
“… where α stands for the absorbance coefficient, A represents the absorbance, and T represents the sample’s thickness. 26 , 38 50 A linear fit to this data reveals that the absorption band edge shifts to the red shift by about 0.2 eV from 3.1 eV for ZnO to 2.9 eV for ZnO/MoS 2 . This redshift possibly occurs from an increase in AgNPs electron density which changes the reflective index of the nanoparticles.…”
Section: Resultsmentioning
confidence: 95%
“…600 nm (arising from exciton A and B transitions), while for ZnO, the absorption peaks are found at 450 nm. After mixing the composite, we found that the MOS 2 /ZnO mix exhibits stronger absorption ability than pristine MoS 2 , suggesting that the heterostructure has more intensive light-matter interaction. ,,, In Figure b, a graph depicting the relationship between the photon energy h ν (eV) and (ν* h ν) 1/ n was plotted, where n is a constant that relates to various electronic transition types ( n = 3 for indirect forbidden transitions, n = 2 for indirect allowed, n = 3/2 for direct forbidden, and n = 1/2 for direct allowed). α false( λ false) = 2.303 log A false( λ false) T where α stands for the absorbance coefficient, A represents the absorbance, and T represents the sample’s thickness. , A linear fit to this data reveals that the absorption band edge shifts to the red shift by about 0.2 eV from 3.1 eV for ZnO to 2.9 eV for ZnO/MoS 2 . This redshift possibly occurs from an increase in AgNPs electron density which changes the reflective index of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…One frequently used vibrational spectroscopy method is Raman scattering [1][2][3][4]. In Raman spectroscopy, only approximately one in 10 6 photons converted into stokes scattering light producing a weak analytical signal intensity [5][6][7][8][9][10]. However, the use of nanostructured materials can increase the efficiency of Raman scattering through plasmonic enhancement to enable single-molecule Raman detection [11,12].…”
Section: Introductionmentioning
confidence: 99%